Fitness cost and realized heritability of resistance to spinosad in Chrysoperla carnea (Neuroptera: Chrysopidae). Issue 6 (December 2014) - Abbas, N.; Mansoor, M.M.; Shad, S.A.; Pathan, A.K.; Waheed, A.; Ejaz, M.; Razaq, M.; Zulfiqar, M.A.
Abstract The common green lacewing Chrysoperla carnea is a key biological control agent employed in integrated pest management (IPM) programs for managing various insect pests. Spinosad is used for the management of pests in ornamental plants, fruit trees, vegetable and field crops all over the world, including Pakistan. A field-collected population of C. carnea was selected with spinosad and fitness costs and realized heritability were investigated. After selection for five generations, C. carnea developed 12.65- and 73.37-fold resistance to spinosad compared to the field and UNSEL populations. The resistant population had a relative fitness of 1.47, with substantially higher emergence rate of healthy adults, fecundity and hatchability and shorter larval duration, pupal duration, and development time as compared to a susceptible laboratory population. Mean relative growth rate of larvae, intrinsic rate of natural population increase and biotic potential was higher for the spinosad-selected population compared to the susceptible laboratory population. Chrysoperla species are known to show resistance to insecticides which makes the predator compatible with most IPM systems. The realized heritability (h2) value of spinosad resistance was 0.37 in spinosad-selected population of C. carnea.